THE IMPLEMENTATION OF EFFECTIVE LEARNING RESOURCES MODELS IN CIVIC EDUCATION LEARNING AT SD NEGERI 5 SUKARARA - Mustakim, Mustakim; Suastika, I Nengah; Sanjaya, Dewa Bagus (Realita : Jurnal Bimbingan dan Konseling, 2024)
The implementation of effective learning resource models in Civic Education (PKn) in elementary schools is crucial. This study aims to explore in-depth the learning resource models that have been implemented in Civic Education at SD Negeri 5 Sukarara, focusing on the analysis of teachers' experiences, students' perceptions, and the understanding of the interaction dynamics between teachers, students, and learning resources within the context of implementing effective learning resource models in Civic Education classes. This research uses a qualitative phenomenological approach with a case study type, involving Civic Education teachers and students of SD Negeri 5 Sukarara as participants. Data were collected through in-depth interviews, observations, and document studies, and analyzed using a thematic approach to identify patterns, themes, and meanings from the collected data. The results show that: 1) Teachers at SD Negeri 5 Sukarara have positive experiences in using effective learning resource models, such as interactive methods like question and answer, TGT, STAD, and CTL. They utilize various learning resources, including the surrounding environment, teaching materials, information technology, and creative media, which enrich students' learning experiences, increase their engagement, and facilitate the understanding of Civic Education concepts. 2) Students respond positively to effective learning resource models, which enhance their engagement and understanding. They find environment-based learning and information technology interesting and relevant, and they enjoy the variety of teaching methods that make learning more interactive and motivate them to learn. 3) The implementation of effective learning resource models creates positive interactions between teachers, students, and learning resources, with teachers acting as facilitators guiding students to interact with various resources. In conclusion, the implementation of effective learning resource models in Civic Education in elementary schools can increase student engagement, peer collaboration, and active participation in discussions, creating a dynamic learning environment that supports better learning outcomes and develops students' social and emotional skills.